2019
DOI: 10.4236/jss.2019.73023
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Krisoker Janala in Disseminating Agricultural Information: An Innovative Tool

Abstract: Krisoker Janala (Farmers Window) is a newly develop app that is used by the agricultural extension agent of Bangladesh to spread information to the farmers. In this regard, the objectives of this study were to assess the effectiveness of Krisoker Janala for disseminating agricultural information and to explore the contributory factors of using Krisoker Janala. Data were collected from 106 Sub Assistant Agriculture Officers (SAAOs) under four upazilas (sub district) of Chuadanga district. A face to face intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The findings are quite rational as using ICT helped farmers to understand and communicate better with AICC personnel regarding agricultural information. Sultana et al, [2] and Pandey [9] found similar findings. They mentioned that ICT helped to disseminate agricultural information for the development of agriculture.…”
Section: Use Of Ictmentioning
confidence: 56%
See 1 more Smart Citation
“…The findings are quite rational as using ICT helped farmers to understand and communicate better with AICC personnel regarding agricultural information. Sultana et al, [2] and Pandey [9] found similar findings. They mentioned that ICT helped to disseminate agricultural information for the development of agriculture.…”
Section: Use Of Ictmentioning
confidence: 56%
“…Nowa-days it is easy to disseminate agricultural information using ICT. The use of ICT as a tool for information dissemination could be regarded as both a driver and an enabler of agricultural information dissemination [2]. ICT has impact on all aspects of life; for instance, it aids timeliness of information dissemination across the country over time, and including bridging of distance and the information gap and mankind.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, the 'Krisoker Janala' smartphone app empowers smallholder farmers to detect and address issues with crops independently, fostering sustainability (Aker & Mbiti, 2010;Sultana et al, 2019) FinTech solutions in real-world agricultural settings may not be fully captured by existing literature. Also, the study highlights the significance of social influence and perceived utility in shaping users' decisions to adopt FinTech services.…”
Section: Fintech In Developing Regionsmentioning
confidence: 99%
“…Agricultural extension has been playing a meaningful role to keep intact the trend of this development. Several public and private organizations offer extension services to the farmers (Sultana et al, 2019). Agricultural extension is considered as one of the main services for capacity building of the farmers in Bangladesh.…”
Section: Muhammad Humayun Kabir* and MD Saiful Islammentioning
confidence: 99%